2016
DOI: 10.1016/j.ebiom.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus and Neuroinflammation in Chronic Inflammatory Demyelinating Polyradiculoneuropathy

Abstract: BackgroundHuman endogenous retroviruses HERV-W encode a pro-inflammatory protein, named MSRV-Env from its original identification in Multiple Sclerosis. Though not detected in various neurological controls, MSRV-Env was found in patients with chronic inflammatory demyelinating polyradiculoneuropathies (CIDPs). This study investigated the expression of MSRV in CIDP and evaluated relevant MSRV-Env pathogenic effects.Methods50 CIDP patients, 19 other neurological controls (ONDs) and 65 healthy blood donors (HBDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 47 publications
4
53
0
1
Order By: Relevance
“…CIDP cases [64], a recent study confirmed upregulated HERV-W expression in blood cells and peripheral nerve lesions of patients suffering from CIDP [80]. This investigation also showed TLR4-mediated effects of HERV-W Env protein on primary human Schwann cells.…”
Section: Microglial Cellsupporting
confidence: 60%
“…CIDP cases [64], a recent study confirmed upregulated HERV-W expression in blood cells and peripheral nerve lesions of patients suffering from CIDP [80]. This investigation also showed TLR4-mediated effects of HERV-W Env protein on primary human Schwann cells.…”
Section: Microglial Cellsupporting
confidence: 60%
“…24 HERV env proteins are related to complex pathological disorders and can be one of the targets for therapeutic approach. 25 A monoclonal antibody against a HERV-W env protein is under clinical trial as a therapeutic approach for MS. 26,27 Upregulation of HERV-W was also reported in blood cells and peripheral nerve lesions of chronic inflammatory demyelinating polyradiculoneuropathy patients, and 28 In sporadic amyotrophic lateral sclerosis patients, env proteins of HERV-K are specifically expressed in cortical and spinal neurons and can cause cellular degeneration. 29 RT proteins encoded by the pol gene of HERV-K have been detected in brain and blood tissues, but transmission of amyotrophic lateral sclerosis has not yet been demonstrated.…”
Section: Endogenous Retroviruses In Human Genomementioning
confidence: 89%
“…Interestingly, it has already been evidenced that HERV-W-Env also displays direct pathogenic effects toward endothelial cells and Schwann cells of peripheral nerves (49,50). This raises questions regarding the comorbidities associated with T1D, such as diabetic vasculopathies and peripheral diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…GNbAC1 is a humanized IgG4 antibody grafted with the 6 complementarity-determining region (CDRs) of an HERV-W-Env-neutralizing clonal hybridoma directed against the HERV-W protein encoded by MSRV-env clone (GenBank, AF331500-1; https://www.ncbi.nlm.nih.gov/genbank/), produced in CHO cells as a recombinant antibody under GMP conditions for therapeutic use. These custom antibodies have already been tested and published in peer-reviewed publications (24,25,30,35,50). GN_mAb_Env04 does not recognize the same epitope that GN_mAb_Env03.…”
Section: Antibodiesmentioning
confidence: 99%